Introduction to Java programming and data structures comprehensive version - Liang, Y. Daniel (Pearson, 2022)
Introduction to Java Programming and Data Structures seamlessly integrates programming, data structures,and algorithms into one text. With a fundamentals-first approach, the textbuilds a strong foundation of basic programming concepts and techniques beforeteaching students object-oriented programming and advanced Java programming.Liang explains programming in a problem-driven way that focuses on problemsolving rather than syntax, illustrating basic concepts by example andproviding a large number of exercises with various levels of difficulty forstudents to practice. The 12th Edition is completely revised in everydetail to enhance clarity, presentation, content, examples, and exercises.